Physical and Chemical Characterization of Granules from 70 % Ethanol Extract of Ganitri Leaves (Eleocarpus serratus L.) using Wet Granulation Method as An Anti-Osteoporosis - Widyowati, Retno; Sari, Romandani Puspita; Retnowati, Dini; Sholikhah, Irawati; Pratama, Rizki Rahmadi (Trends in Sciences, 2024)
Elaeocarpus serratus L. leaves have been used as an antiosteoporosis treatment and it contains active compounds such as quercetin, rutin, and myricetin. The pre-formulation study was done by making granules from 70 % ethanol extract of this plant through the wet granulation method. These granules were determined by physical characteristics including organoleptic, flow properties, real and incompressible specific gravity, moisture, particle size distribution, and chemical characteristics including flavonoid content. The organoleptic result showed that all formulas had a strong characteristic odor and a slightly bitter taste. Formula A had a dark brown color, while formulas B and C were whitish brown. Based on the results of the flow properties test, all formulas had good flow properties because they had gone through the granulation process. The compressibility index, Hausner ratio, and % moisture content displayed that all formulas met the requirements and had almost the same value. In the assay process, the average % w/w content of formula A was 0.68 ± 0.017 %, formula B was 0.66 ± 0.044 %, and formula C was 0.16 ± 0.006 %. The most optimum formula was formula C with whitish brown color, slightly bitter taste, and strong odor, 10.90 ± 0.000 g/s of flow rate, 25.41 ± 0.000 ° of angle, 4.36 ± 0.214 % of moisture content, 13.80 % compressibility index, 1.1601 of Hausner ratio, 1772.04 µm of particle average distribution, and 0.66 ± 0.044 % w/w of percent routine flavonoid content. HIGHLIGHTS This study aims to determine the characteristics of granules from 70 % ethanol extract of ganitri leaves (Elaeocarpus serratus), the optimal formula to make granule preparations with active ingredients of ganitri leaves, and the levels of flavonoids using the spectrophotometer method. It also determined the characteristic physics of granule preparations including flow properties, organoleptic, moisture, particle size distribution, and real and incompressible specific gravity. GRAPHICAL ABSTRACT